2021
DOI: 10.3390/ijerph182312780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Home Confinement on Behavior, Perception of Threat, Stress and Training Patterns of Olympic and Paralympic Athletes

Abstract: Background: The aims of this study were to analyze the effects of the COVID-19 pandemic and its subsequent confinement on behaviors, perception of threat, stress, state of mind and training patterns among Olympic and Paralympic level athletes. Methods: Data gathering was performed utilizing an online questionnaire during imposed confinement. A correlational design with incidental sampling for convenience was used. All the variables were analyzed by age, gender, academic training, type of participation and spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 21 publications
3
21
1
Order By: Relevance
“…One possible explanation for these results is that the sample in our study was composed entirely of the best elite athletes within a country, as opposed to the aforementioned studies, and top-level athletes may have much more psychological training and experience from years of competition, which allows the equalisation of the levels of anxiety symptoms between men and women. In fact, when male and female Olympic and Paralympic athletes were analysed during the COVID-19 crisis, no differences were found in anxiety symptoms levels [30,31]. Likewise, another study compared male and female soccer professionals, that is, elite players, during the COVID-19 pandemic, and the results indicated that state anxiety and trait anxiety in males were greater than in females, on average [18].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…One possible explanation for these results is that the sample in our study was composed entirely of the best elite athletes within a country, as opposed to the aforementioned studies, and top-level athletes may have much more psychological training and experience from years of competition, which allows the equalisation of the levels of anxiety symptoms between men and women. In fact, when male and female Olympic and Paralympic athletes were analysed during the COVID-19 crisis, no differences were found in anxiety symptoms levels [30,31]. Likewise, another study compared male and female soccer professionals, that is, elite players, during the COVID-19 pandemic, and the results indicated that state anxiety and trait anxiety in males were greater than in females, on average [18].…”
Section: Discussionmentioning
confidence: 95%
“…The results of studies carried out with Olympic and Paralympic athletes during the COVID-19 health crisis showed differences depending on the level of education, with athletes with university education having a more positive assessment of the situation than athletes with a lower level of education [31]. Likewise, another study with a similar sample of athletes observed that the group of athletes with professional training was more worried about a reduction in their athletic ability because of the confinement than the group with only a university education [30].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…At the individual level, alterations have been evidenced in habitual practices, work, interpersonal relations, health and leisure, and sports, among others, which affect the physical and psychological health of people [ 5 , 6 , 9 ]. Several publications have reported the interest in this topic by researchers who have studied SARS-CoV-2 in athletes from different sports disciplines: Olympic and Paralympic [ 12 ] elites and semi-elites [ 13 , 14 , 15 ]; athletes [ 16 ]; handball players [ 17 ]; chess players [ 18 ]; or martial arts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to global public health data, physical activity levels were considered a widespread problem due to the lack of practice before the COVID-19 pandemic [ 12 ]. In Latin America, especially in Colombia, citizens between 18 and 64 years old were inactive according to the guidelines from the World Health Organization.…”
Section: Introductionmentioning
confidence: 99%